Dolphin ride - Jill Atkins (London, Franklin Watts, 2019)
Lexi and her dad are on a boat trip to spot dolphins. And when Lexi makes a wish to ride a dolphin, she is taken on a magical dream ride.Reading Champion offers independent reading books for children to practise and reinforce their developing reading skills .Fantastic, original stories are accompanied by engaging artwork and a reading activity. Each book has been carefully graded so that it can be matched to a child's reading ability, encouraging reading for pleasure